Forecasting of The Crime Rate Using Automatic Clustering and Fuzzy Logic Relationship Method In North Sumatra - Elsyah Suhadiyah; Sajaratud Dur; Hendra Cipta (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Currently the crime rate is very alarming and reported in various mass and electronic media. The high crime rate in the Province of Nort Sumatra is very unsettling for the community. The purpose of this research is to get the result of forecasting the crime ratel in the 2021 - 2024 using Automatic Clustering And Fuzzy Logic Relationship (ACFLR) method. The advantage of this method is that the method has a high level of accuracy because the Mean Absolute Percentage Error (MAPE) value is relative small and the results of forecasting analysis obtained in 2021 there are 31522 cases, in 2022 are 31533 cases, in 2023 are 31574 cases and the last one in 2024 was 31602 cases. In addition, the prediction error rate MAPE obtained is 0,35 % Keywords: Crime rate, Automatic Clustering And Fuzzy Logic Relationship.